Baukunst 4. - Copans, Richard, ....-; Neumann, Stan, 1949- ([s.l.] : Arte editions, 2005)
Claude-Nicolas LEDOUX: Die Saline von Arc-et-Senans. - Pierre CHAREAU: Das Glashaus. - Frank O. GEHRY: Bilbao Guggenheim Museum. - Jean PROUVÉ: Das Haus von Jean Prouvé. - Toyo ITO: Die Sendaï-Mediathek. Die Abtei Sainte Foy de Conques.
Keywords: Architectuurgeschiedenis; Bouwkunst